G251(P) Throwing Money Away: Staff Awareness of Everyday Equipment Waste. (24th May 2017) - Salkind, J; Knight, K; Shahrad, B; Daniels, J
Abstract : Aims: At a national level, there is huge debate around NHS funding. With this in mind, we planned a local project focussing on saving money through reducing unnecessary waste of commonly used clinical items. Our aims were to assess staff awareness of equipment costs and their current attitudes toward disposal of unused equipment. Methods: An anonymous online questionnaire was distributed to all paediatric doctors and nurses. We asked staff about their current practice and to estimate the cost of 14 commonly used items (e.g. cannulas, gauze and needles) and the disposal of clinical waste. Costs for each item were obtained from the procurement department. Staff were asked about their behaviours around use and disposal of clinical items, and for each question asked to rate their practice on a 5-point Likert scale where never=1 and always=5. Average scores out of 5 were calculated to assess frequency of behaviours. Results: 40 staff members completed the questionnaire. When assessed by group, nurses thought about equipment cost the most (average 4.2/5) compared with doctors (average 2.8/5). Junior doctors most commonly took spare items with them for a procedure (average 4.2/5), followed by senior doctors (average 3.9/5) and then nurses (average 2.8/5). Across all groups, staff had low rates of throwing away unopened spare equipment (average 1.8/5) and putting non-sharp items in the sharps bin (average 2/5). All staff overestimated the cost of 13 out of 14 items and also overestimated the cost of waste disposal. Conclusion: The fact that staff overestimated the price of all but one clinical item indicates poor awareness of the cost of commonly used consumables. Doctors tended not to think about the price of items used during their everyday practice, and therefore waste money throwing items away. If these attitudes are commonplace throughout the healthcare system, this could account for a vast amount of money wasted annually. We took action locally by adding visible price labels in the stock room and produced posters to educate staff on tips to reduce waste. Our resurvey will assess whether increased price awareness translates into a change in clinical practice.